Pro-environmental behavior and public understanding of climate change - Masud, Muhammad Mehedi; Akhtar, Rulia; Rafia, Afroz; Al-Amin, Abul Quasem; Kari, Fatimah (Springer Science+Business Media Dordrecht, 2015)
The aim of this article is to examine whether awareness, knowledge and risk perception of climate change have significant influence on attitudes and pro-environmental behaviour. The study found that awareness, knowledge and risk perception of climate change positively influence the formation of favourable attitudes future action climate change. In addition, this paper also found mediated relationship through attitudes between awareness, knowledge, risk perception and pro-environmental behaviour. The paper argues that people are more likely to accept pro-environmental behaviours only if they have sufficient understanding of the adverse impacts of no action. This study offers decision makers field data to formulate relevant environmental policies and strategies in Malaysia.